Surface Morphology and Modulus, Wetting Behavior and Photocatalytic Activity of the TiO2 Coated Materials Based on PMMA/O-MMT Composite Microfibers (Journal of Fiber Bioengineering and Informatics, 2018)
Poly(Methyl Methacrylate) PMMA/Organically Modified Montmorillonite (O-MMT) compositemicrofibers membrane coated with TiO_2 has significant advantages in cationic dyes adsorption andcan break down the adsorbed dyes under UV radiation, which is quite useful in water treatment. In thiswork, PMMA/O-MMT composite microfibers were firstly prepared by emulsion polymerization combinedwith electrospinning, and then coated by nanosize TiO_2 using RF magnetron sputtering. The effectsof TiO_2 sputter coating on morphology and surface modulus was characterized by Scanning ElectronMicroscope (SEM) and Atomic Force Microscopy (AFM), while the wetting behaviour was studied bydrop shape analyzer. The photocatalytic degradation of methylene blue was tested under UV radiationand the properties of the treated and untreated samples were compared. It was observed from SEMimages that TiO_2 was well dispersed and deposited on the surface of PMMA/O-MMT microfibers, whilethe AFM results showed increase in the surface modulus after TiO_2 coating. Besides, the wettability ofthe microfibers membrane coated with TiO_2 was altered, which facilitated water treatment in practicaluse. Furthermore, the PMMA/O-MMT microfibers membrane coated with TiO_2 performed well inphotocatalytic degradation of methylene blue. In conclusion, PMMA/O-MMT composite microfibersmembrane coated with TiO_2 was quite promising in water treatment.
Keywords: Electrospinning; RF (Ratio Frequency) Magnetron Sputtering; TiO_2; Microfibers; Water Treatment